2013
DOI: 10.1208/s12248-013-9478-2
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Models of Diffusive Nanoparticle Transport in 3-Dimensional Tumor Cell Spheroids

Abstract: Abstract. The rapidly evolving nanotechnology field highlights the need of better understanding the relationship between nanoparticle (NP) properties and NP transport in solid tumors. The present study tested the hypothesis that the diffusive transport and spatial distribution of NP can be predicted based on the following parameters: interstitial NP diffusivity, NP-cell interaction parameters (cell surface binding capacity, rate constants of association, dissociation, and internalization). We (a) established t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
97
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(104 citation statements)
references
References 43 publications
7
97
0
Order By: Relevance
“…Accordingly, an investigator can predict the delivery and residence of a drug at the intended target sites based on the numerical values of model parameters that are readily measured in vitro or ex vivo (e.g., drug-cell-protein interactions can be measured using cultured tumor cells) or in vivo (e.g., whole-body pharmacokinetics). Another area of potential utility is cancer nanotechnologies, as we have shown that the three-dimensional diffusive transport of nanoparticles with different sizes and surface charges in tumor spheroids can be predicted based on biointerface parameters measured in monolayer cultures (51).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, an investigator can predict the delivery and residence of a drug at the intended target sites based on the numerical values of model parameters that are readily measured in vitro or ex vivo (e.g., drug-cell-protein interactions can be measured using cultured tumor cells) or in vivo (e.g., whole-body pharmacokinetics). Another area of potential utility is cancer nanotechnologies, as we have shown that the three-dimensional diffusive transport of nanoparticles with different sizes and surface charges in tumor spheroids can be predicted based on biointerface parameters measured in monolayer cultures (51).…”
Section: Discussionmentioning
confidence: 99%
“…Diffusivity in tumor tissue D′ and diffusivity in tumor interstitium D int were calculated using paclitaxel diffusion coefficient in aqueous solution D aqueous , radii of paclitaxel (r s ) and interstitial matrix protein fiber (r f ), volume fraction of interstitial matrix F im , and tortuosity τ (11,34,48) (51). For tortuosity, we used the value of 2.5 established for rat cerebellum and rat peritoneal tissue (11,33).…”
Section: Model Development: Transport Equationsmentioning
confidence: 99%
“…109,110 They separated parameters affecting drug transport in the MCTS into two groups: the parameters depending on liposome to cell interactions (binding constants, uptake and retention rates, termed NP-cell biointerface parameters) and the diffusivity parameters related to MCTS environment (cell and ECM density) and NP characteristics (size, shape, etc.). Gao et al 109 successfully simulated diffusion of negatively charged polystyrene beads, near-neutral liposomes and positively charged liposomes with respective diameters of 20, 110 and 130 nm in 3D pharynx FaDu tumor spheroids, while Wientjes et al 110 achieved excellent precision in the prediction of the diffusion of NPs with various sizes (20-135 nm) and surface charges (-49 to +44 mV) in MCTS. Finally, very recently, Curtis et al examined the cytotoxicity of novel two-and three-layer gold NPs in heterogeneously vascularized tumors for future in vivo evaluation.…”
Section: Multicellular Tumor Spheroids In Nanomedicine Screeningmentioning
confidence: 99%
“…17,18 Recent studies have shown that modified micelles can penetrate deeper and deliver more drugs into MCTS resulting in higher toxicity to the spheroids. [15][16][17][18][19][20][21] However, one important factor that has been ignored is the micelle trafficking inside the MCTS, which revolves around how micelles pass through the peripheral cells and their surrounding extracellular matrix (ECM) networks. Due to the abnormal vascular structure of the tumor tissue, this population of cells has a typical distance of more than 100 µm from the blood vessel.…”
Section: Introductionmentioning
confidence: 99%